The Implementation Hybrid Learning Method for English Language Learning at AMA Yogyakarta - Andhina Ika Sunardi; Nafisatul Lutfi (Universitas Muhammadiyah Kalimantan Timur, 2022)
The current technological development has entered the 4.0 industrial revolutions. This revolution encouraged automation systems in almost all activities and processes . The time constraint for face-to-face interactions in the classroom often makes English learning becomes less effective, especially for classes with diverse levels of English proficiency. In a higher education system which demands active learning, English teachers often find it difficult to help students whose English language competence is below average . In fact , the target of learning English on campus is generally quite high. One of the solutions is that the teaching and learning process uses hybrid method- a learning system that complements face-to-face interactions in the classroom along with distant learning using the internet. Hybrid learning is able to complement the lack of time for face-to-face interactions in the classroom in the form of distance learning with the medium of internet. This paper is the result of the writer’s observations in applying this method when teaching the first semester of the 2021/2022 study period AMA Yogyakarta. This research is a descriptive quantitative research using questionnaires as the data retrieval technique. This research concludes that hybrid learning method can be used in English learning classes with 61,26% of students agree to the method, and 38,7% do not agree even though in general, they prefer face to face interaction. However, it can be a solution for distant learning since it is accessible anytime and anywhere although it requires stable internet connection as its basic requirements. Keywords : Hybrid learning , English learning , Descriptive.